THE ROLE OF ABU MU'IN AN-NASAFI SHRINE IN THE DEVELOPMENT OF TOURISM (Proceedings of International Educators Conference, 2024)
This article contains information about the life and work of Abu Muin al-Nasafi, a prominent scholar of the Islamic world, his scientific works and their place in the Islamic world, as well as information about the pilgrimage site where the scholar settled and his role in the development of tourism in Kashkadarya. is given.